2014
DOI: 10.1186/s13048-014-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tissue cryopreservation followed by controlled ovarian stimulation and pick-up of mature oocytes does not impair the number or quality of retrieved oocytes

Abstract: BackgroundThe objective of this study was to evaluate the feasibility of fertility preservation in cancer patients by combined bilateral ovarian cortex cryopreservation and embryo freezing.MethodsThis was a cohort-controlled study in a university hospital center. Sixteen patients with a recent cancer diagnosis were included in the study. They all consented to fertility preservation by a combined technique: ovarian tissue cryopreservation (OTC) followed by ovarian stimulation for in vitro fertilization (IVF) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 32 publications
1
28
0
2
Order By: Relevance
“…The mean number of stored embryos per patient in this study was 4.06 (±3.68), apparently similar to a control group in one of our previous studies during the same period [17]. In this control group, the mean number of goodquality frozen embryos obtained per patient on day 3 was 4.4, compared to 4.06 in the present study.…”
Section: Number Of Oocytes and Embryossupporting
confidence: 88%
“…The mean number of stored embryos per patient in this study was 4.06 (±3.68), apparently similar to a control group in one of our previous studies during the same period [17]. In this control group, the mean number of goodquality frozen embryos obtained per patient on day 3 was 4.4, compared to 4.06 in the present study.…”
Section: Number Of Oocytes and Embryossupporting
confidence: 88%
“…Minimal stimulation with gonadotropins before ovariectomy might stimulate follicles to grow and more competent oocytes could potentially be obtained. COS followed by hCG maturation trigger and oocyte retrieval 34-36 h later, combined with ovarian tissue biopsy after oocyte retrieval has been described [46], however with a negative impact on the quality of ovarian tissue for cryopreservation [47].…”
Section: Discussionmentioning
confidence: 99%
“…It was indeed recently demonstrated that the number of oocytes obtained after COS, following immediately OTC, was similar to a control group of the same age [14].…”
Section: Live Birthmentioning
confidence: 99%